2016
DOI: 10.1108/ijph-05-2014-0011
|View full text |Cite
|
Sign up to set email alerts
|

Injecting drug use, sexual risk, HIV knowledge and harm reduction uptake in a large prison in Bali, Indonesia

Abstract: This is the first study reporting HIV-related risk behavior from an Indonesian prison with an established methadone substitution program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…No records are kept of the number of drug injecting prisoners. However, a study in Kerobokan Prison (Bali) reported 7.4 % of 230 prisoner participants had injected drugs while in prison, of whom 47% had also shared needles with between two and ten other prisoners (Sawitri et al 2016).…”
mentioning
confidence: 99%
“…No records are kept of the number of drug injecting prisoners. However, a study in Kerobokan Prison (Bali) reported 7.4 % of 230 prisoner participants had injected drugs while in prison, of whom 47% had also shared needles with between two and ten other prisoners (Sawitri et al 2016).…”
mentioning
confidence: 99%
“…This perception contrasts with the evidence that HIV transmission is more common in prison settings because of the much higher frequency of sharing injecting equipment (Culbert et al, 2015;Indig et al, 2010;Ju ¨rgens et al, 2009). Furthermore, this association has been reported (Dolan et al, 2015) both for prisons situated in high-income countries (Lindbom et al, 2017) and for middle-income countries including Indonesia (Sawitri et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…Also, personal and psychosocial factors appear to in uence sexual risk behavior among PWID while possibly playing a role in promoting sexual risk behavior among MWID. [11][12][13] In addition, aggressive policing tactics and harassment that re ect government-enacted stigma toward migrants and MWID may form a "driving force" that increases MWID engagement in HIV sexual risk behavior. 14 Consequently, in addition to examining HIV knowledge and self-perceived risk, the analysis also investigates the possible effects of demographic and key psychosocial factors (depression, loneliness, and societal stigma toward migrants as manifested through police harassment) on sexual risk behavior.…”
Section: Introductionmentioning
confidence: 99%